Cladding-bidirectional nitriding combined machining method based on 30CrMnSiA steel

Through the cladding-bidirectional nitriding composite processing method, the surface and near-surface structure of the hardness gradient are formed, and the problem of poor wear resistance, high temperature resistance and corrosion resistance of 30CrMnSiA steel under high temperature environment and corrosion conditions is solved, and the problem of poor wear resistance, high temperature resistance and corrosion resistance of 30CrMnSiA steel is achieved. Various excellent performance improvements of the materials.

CN119433154APending Publication Date: 2025-02-14CHANGHE AIRCRAFT INDUSTRIES CORPORATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411518470.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

30CrMnSiA steel has poor wear resistance, high temperature resistance and corrosion resistance under high temperature environment and corrosion conditions, and it is difficult to work stably for a long time.

Method used

The cladding-bidirectional nitriding composite processing method is adopted to form surface and near-surface structures with hardness gradient through steps such as tempering treatment, ionic nitriding, laser cladding, flame quenching, etc., to improve the wear resistance, high temperature resistance and Corrosion resistance.

Benefits of technology

It significantly improves the wear resistance, high temperature resistance and corrosion resistance of 30CrMnSiA steel, so that it can work stably for a long time under high temperature environment and corrosion conditions, replacing the use of some medium and high alloy steels.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a cladding-bidirectional nitriding combined machining method based on 30CrMnSiA steel. The cladding-bidirectional nitriding combined machining method comprises the following steps: step 1, carrying out thermal refining on the 30CrMnSiA steel; 2, ion nitriding treatment is carried out on the 30CrMnSiA steel; 3, after nitriding is completed, preheating is conducted at the heating temperature T2, and the heat preservation time is S2; step 4, carrying out laser cladding treatment on the surface of the nitrided sample; 5, after cladding is completed, heat preservation is conducted at the heating temperature T4 for the heat preservation time S3, the heating temperature is increased to T5 for the heat preservation time S4, and circulation is conducted N times; 6, flame quenching is conducted on the surface layer of the machined sample, the moving speed is controlled to be V4, and the purpose is to improve the structure of the surface layer; and 7, the total nitriding layer depth reaches D4, the nitriding layer hardness is H, and the pitting potential is increased to E or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of aviation, and in particular to a cladding-bidirectional nitriding composite processing method based on 30CrMnSiA steel. Background Art

[0002] 30CrMnSiA steel is a commonly used alloy structural steel with good mechanical properties and machinability. It is often used to manufacture bolts, joints and other load-bearing parts. However, it has average wear resistance, poor high temperature resistance, and is very prone to corrosion. It cannot work stably for a long time in high temperature environments and corrosive conditions. Directly cladding TC4 titanium alloy and nitriding can prepare a TiN strengthening layer, but it is prone to brittle peeling. Summary of the invention

[0003] The present application provides a cladding-bidirectional nitriding composite processing method based on 30CrMnSiA steel, which can solve the problem that 30CrMnSiA steel has poor high temperature resistance and is very susceptible to corrosion.

[0004] Technical solution: A cladding-bidirectional nitriding composite processing method based on 30CrMnSiA steel, comprising:

[0005] Step 1: 30CrMnSiA steel is quenched and tempered to obtain tempered martensite, bainite, troostite and other structures to prepare for the next step of nitriding;

[0006] Step 2: ion nitriding treatment is performed on 30CrMnSiA steel, wherein: vacuum degree M, nitrogen volume content in the atmosphere is controlled at A%, hydrogen volume content is controlled at B%, argon volume content is controlled at C%, furnace heating temperature T1, holding time S1, and nitriding layer depth D1, in preparation for bidirectional nitriding process;

[0007] Step 3: After nitriding is completed, it is recommended to preheat at heating temperature T2 and hold for time S2. The temperature parameter selection needs to consider both controlling the further diffusion of nitrogen atoms and preheating of the laser cladding process.

[0008] Step 4: The surface of the sample after nitriding is subjected to laser cladding treatment, the cladding material is TC4 titanium alloy, the laser power is P, the defocus amount is L, the scanning speed is V1, the delivery rate is V2, the overlap rate is D, and the protective gas argon flow rate is V3, and a cladding layer with a thickness of D2 is obtained, and it is processed to a thickness of D3;

[0009] Step 5: After the cladding is completed, keep the temperature at T4 for S3, then increase the temperature to T5 for S4, and repeat N times;

[0010] Step 6: flame quench the surface of the processed sample, and control the moving rate to V4, in order to improve the structure of the surface;

[0011] Step 7: The overall nitriding layer depth reaches D4, the nitriding layer hardness is H, and the pitting potential is increased to above E.

[0012] Specifically, step 2 includes:

[0013] Step 21: Ion nitriding uses nitrogen-hydrogen mixed gas as the process gas, and the supply amount of ion nitriding process gas is set to 0.05m 3 / h~0.6m 3 / h;

[0014] Step 22: using a nitrogen-hydrogen mixed gas as the process gas, wherein the volume content A of the nitrogen is set to 35%-55%, the volume content B of the hydrogen is set to 55%-35%, and the volume content C of the argon is set to 10%;

[0015] Step 23: Process the parts by mechanical processing, and the surface appearance of the parts shall be free from defects such as rust, scratches, and bumps, and the roughness of the surface to be infiltrated shall not be greater than 0.8 μm;

[0016] Step 24: Set the vacuum degree M to 10 -1 to 10 -3 Pa, the gas pressure in the furnace during the insulation stage ranges from 100Pa to 1300Pa;

[0017] Step 25: The heating temperature in the furnace is T1, and the insulation time is S1;

[0018] Step 26: After the insulation stage is over, cut off the glow power supply, close the valve to stop gas supply and exhaust, and the workpiece cools down with the furnace. The workpiece can be taken out of the furnace only when the temperature drops below 150°C;

[0019] Step 27: Detect the depth of the penetration layer, and the penetration layer depth D1 is controlled within the range of 1.0-1.5 mm;

[0020] Step 28: Detect the structure of the nitrided layer. The near-surface layer is γ′ phase and ε phase. Cr2N and CrN compounds can be formed on the surface. The content of the CrN compound is controlled to be above 75%;

[0021] Step 29: If the content of CrN compound is lower than 75%, the nitrogen volume content A is set to the upper limit of the recommended value, and the nitriding temperature T1 is increased to 580-630°C.

[0022] Specifically, step 3 includes:

[0023] Step 31: Use an air furnace to heat the nitrided sample, select the temperature T2, the heating temperature shall not exceed T3, the insulation time is S2, and cool with the furnace;

[0024] Step 32: Detect the microstructure of the nitriding layer. The near-surface layer is γ′ phase and ε phase. Cr2N and CrN compounds can be formed on the surface. The content of the CrN compound is controlled to be above 75%.

[0025] Step 33: If the content of CrN compound is less than 75%, a part of CrN compound has been converted into Cr2N, and supplementary nitriding is performed again;

[0026] Step 34: Supplementary nitriding process, supplementary nitriding holding time S5;

[0027] Step 35: Check the microstructure of the nitriding layer. The near-surface layer is γ′ phase and ε phase. Cr2N and CrN compounds can be formed on the surface, wherein the content of the CrN compound is controlled to be above 75%.

[0028] Specifically, step 4 includes:

[0029] Step 41: Before the cladding process, the TC4 alloy powder is dried to prevent the powder from agglomerating and affecting fluidity;

[0030] Step 42: Select the following process parameters: laser power P is 2200-3000W, defocus L is 0±3mm, scanning speed V4, powder feeding rate V2, overlap rate D is 40%-55%, shielding gas flow rate V3, double or triple cladding, and control the cladding layer thickness D2 within the range of 0.6-1.0mm;

[0031] Step 43: remove the cladding layer on the surface by mechanical processing, and control the cladding layer D3 after processing to be within the range of 0.2-0.3 mm, and the surface roughness is not greater than 0.8 μm.

[0032] Specifically, step 5 includes:

[0033] Step 51: according to the heating temperature T4, the holding time S3, the heating temperature T5, the holding time S40.5h, the number of cycles N is set to 3-7 times;

[0034] Step 52: Check the appearance and organizational composition of the surface of the cladding layer. The surface should be golden yellow and covered with certain titanium nitrides, including Ti3N, Ti2N, and TiN. The content of TiN needs to be controlled at 30%-60%.

[0035] Specifically, step 6 includes:

[0036] The surface of the sample clad with TC4 titanium alloy was flame quenched again, and the moving speed V4 was controlled within the range of 40-60 mm / min to increase the depth of the infiltration layer and adjust the structure in the cladding layer.

[0037] Specifically, step 7 includes:

[0038] The overall nitriding layer depth reaches D4 of 1.5mm-2.0mm, the nitriding layer hardness H is 1050-1350HV, and the pitting potential is increased to E of more than 900mV.

[0039] Specifically, the heating temperature T1 is set to 480°C-550°C;

[0040] The heating temperature T2 is set to 200°C-350°C;

[0041] The heating temperature T3 is set to 400°C;

[0042] The heating temperature T4 is set to 750°C;

[0043] The heating temperature T5 was set to 800°C.

[0044] Specifically, the holding time S1 is set to 6-12h;

[0045] The holding time S2 is set to 1-2h;

[0046] The holding time S3 is set to 1h;

[0047] The holding time S4 ​​is set to 0.5h;

[0048] The holding time S5 is set to 1-3h.

[0049] Specifically, the scanning speed V1 is 600-800 mm / min;

[0050] Scanning speed V4 is 600-1100 mm / min;

[0051] The powder feeding rate V2 is 8-15g / min;

[0052] The protective gas flow rate V3 is 6-8L / min.

[0053] In summary, the present application provides a cladding-bidirectional nitriding composite processing method based on 30CrMnSiA steel, which forms different compounds on the surface and near-surface of 30CrMnSiA steel, forming a certain hardness gradient, which can effectively improve the wear resistance, high temperature resistance and corrosion resistance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] none DETAILED DESCRIPTION

[0055] The present application provides a cladding-bidirectional nitriding composite processing method based on 30CrMnSiA steel, which imparts 30CrMnSiA steel with multiple excellent properties.

[0056] 30CrMnSiA steel is a commonly used alloy structural steel. Through the cladding-bidirectional nitriding composite processing method, by controlling the atmosphere composition of the nitriding process, specific surface and near-surface structures can be obtained to prepare high-quality surface coatings.

[0057] The present application provides a cladding-bidirectional nitriding composite processing method based on 30CrMnSiA steel, comprising the following steps:

[0058] Step 1: 30CrMnSiA steel is quenched and tempered to obtain tempered martensite, bainite, troostite and other structures to prepare for the next step of nitriding;

[0059] Step 2: ion nitriding treatment is performed on 30CrMnSiA steel, wherein: vacuum degree M, nitrogen volume content in the atmosphere is controlled at A%, hydrogen volume content is controlled at B%, argon volume content is controlled at C%, furnace heating temperature T1, holding time S1, and nitriding layer depth D1, in preparation for bidirectional nitriding process;

[0060] Step 3: After nitriding is completed, it is recommended to preheat at heating temperature T2 and hold for time S2. The temperature parameter selection needs to consider both controlling the further diffusion of nitrogen atoms and preheating of the laser cladding process.

[0061] Step 4: The surface of the sample after nitriding is subjected to laser cladding treatment, the cladding material is TC4 titanium alloy, the laser power is P, the defocus amount is L, the scanning speed is V1 600-800 mm / min, the feed rate is V2, the overlap rate is D, the protective gas argon flow rate is V3, and a cladding layer with a thickness of D2 is obtained, and it is processed to a thickness of D3;

[0062] Step 5: After cladding is completed, keep warm at heating temperature T4 for S3, raise heating temperature to T5, keep warm for S4, repeat N times. The selection of temperature and time should consider accelerating the diffusion of nitrogen atoms (i.e., achieving bidirectional nitriding), eliminating various stresses of laser cladding process, and avoiding excessive growth of grains.

[0063] Step 6: The surface of the processed sample is flame quenched and the moving rate is controlled to V4 in order to improve the surface structure.

[0064] Step 7: The overall nitriding layer depth can reach D4, the nitriding layer hardness is H, and the pitting potential is increased to above E.

[0065] Specifically, step 2 includes:

[0066] Step 21: Ion nitriding uses nitrogen-hydrogen mixed gas as the process gas, and the supply amount of ion nitriding process gas is set to 0.05m 3 / h~0.6m 3 / h.

[0067] Step 22: Use nitrogen-hydrogen mixed gas as process gas, with the nitrogen volume content A set to 35%-55%, the hydrogen volume content B to 55%-35% (i.e., the recommended volume ratio of nitrogen to hydrogen is close to 1:1), and the argon volume content C to 10%.

[0068] Step 23: The parts are processed by mechanical processing, and the surface appearance of the parts has no defects such as rust, scratches, and bumps, and the roughness of the surface to be infiltrated is not greater than 0.8μm.

[0069] Step 24: Set the vacuum degree M to 10 -1 to 10 -3 Pa, the gas pressure in the furnace during the insulation stage ranges from 100Pa to 1300Pa.

[0070] Step 25: The heating temperature T1 in the furnace is set to 480°C-550°C, and the insulation time S1 is set to 6-12h.

[0071] Step 26: After the insulation stage, cut off the glow power supply, close the valve to stop gas supply and exhaust, and the workpiece cools down with the furnace. The workpiece can be taken out of the furnace only when the temperature drops below 150°C.

[0072] Step 27: Detect the depth of the penetration layer, and the penetration layer depth D1 is controlled within the range of 1.0-1.5 mm.

[0073] Step 28: Check the structure of the nitrided layer. The near-surface layer is composed of γ′ phase and ε phase. Cr2N and CrN compounds can be formed on the surface, and the content of the CrN compound is controlled to be above 75%.

[0074] Step 29: If the content of CrN compounds is lower than 75%, the nitrogen volume content A can be set to the upper limit of the recommended value, and the nitriding temperature T1 can be increased to 580-630°C.

[0075] Specifically, step 3 includes:

[0076] Step 31: Use an air furnace to heat the nitrided sample, select the temperature T2 as 200℃-350℃, the heating temperature must not exceed T3 (i.e. 400℃), the insulation time S2 is 1-2h, and cool with the furnace.

[0077] Step 32: According to step 28, the structure of the nitriding layer is detected, which must meet the requirement that the content of CrN compounds is controlled to be above 75%.

[0078] Step 33: If the content of CrN compounds is lower than 75%, a portion of the CrN compounds has been converted into Cr2N, and additional nitriding is required.

[0079] Step 34: The supplementary nitriding process is specifically carried out according to the requirements in step 2, and the insulation time S5 of the supplementary nitriding is changed to 1-3h.

[0080] Step 35: According to step 28, the structure of the nitriding layer is detected, which must meet the requirement that the content of CrN compounds is controlled to be above 75%.

[0081] Specifically, step 4 includes:

[0082] Step 41: Before the cladding process, the TC4 alloy powder is dried (process parameters: 150°C, 40min-80min) to prevent powder agglomeration from affecting fluidity.

[0083] Step 42: Select the following process parameters: laser power P is 2200-3000W, defocus L is 0±3mm, scanning speed V4 is 600-1100mm / min, powder feeding rate V2 is 8-15g / min, overlap rate D is 40%-55%, protective gas (argon) flow rate V3 is 6-8L / min, double or triple cladding is performed, and the cladding layer thickness D2 is controlled within the range of 0.6-1.0mm.

[0084] Step 43: remove the cladding layer on the surface by mechanical processing, and control the cladding layer D3 after processing to be within the range of 0.2-0.3 mm, and the surface roughness is not greater than 0.8 μm.

[0085] Specifically, step 5 includes:

[0086] Step 51: The heating temperature T4 is set to 750°C, the holding time S3 is set to 1h, the heating temperature T5 is set to 800°C, the holding time S4 ​​is set to 0.5h, and the number of cycles N is set to 3-7 times.

[0087] Step 52: Check the appearance and organizational composition of the surface of the cladding layer. The surface should be golden yellow and covered with a certain amount of titanium nitride, mainly Ti3N, Ti2N, and TiN, wherein the content of TiN needs to be controlled at 30%-60%.

[0088] Step 53: Generally, when cycle N is set to 3 times, the TiN content can reach more than 30%; when cycle N is set to 5 times, the TiN content can reach more than 50%; when cycle N is set to 7 times, the TiN content can reach more than 53%, and the increase is not large.

[0089] Specifically, step 6 includes: flame quenching the surface of the sample clad with TC4 titanium alloy, controlling the moving speed V4 within the range of 40-60 mm / min, which can further increase the depth of the infiltration layer and adjust the structure in the cladding layer;

[0090] Specifically, step 7 includes: the overall nitriding layer depth can reach D4 of 1.5mm-2.0mm, the nitriding layer hardness H is 1050-1350HV, and the pitting potential is increased to E of more than 900mV.

[0091] In summary, this patent proposes a cladding-bidirectional nitriding composite processing method based on 30CrMnSiA steel, and prepares 30CrMnSiA structural steel materials with high wear resistance, high temperature resistance and corrosion resistance. The advantage of this invention is that compared with the 30CrMnSiA steel body, it is endowed with a variety of excellent properties, so that it can work stably for a long time in high temperature environment, corrosive environment, and easy wear conditions, and can replace some medium and high alloy steels, and further expand the application scenarios of this material.

Claims

1. A cladding-bidirectional nitriding composite processing method based on 30CrMnSiA steel, characterized in that: Methods include: Step 1: 30CrMnSiA steel is quenched and tempered to obtain tempered martensite, bainite and troostite structures, in preparation for the next step of nitriding; Step 2: ion nitriding treatment is performed on 30CrMnSiA steel, wherein: vacuum degree M, nitrogen volume content in the atmosphere is controlled at A%, hydrogen volume content is controlled at B%, argon volume content is controlled at C%, furnace heating temperature T1, holding time S1, and nitriding layer depth D1, in preparation for bidirectional nitriding process; Step 3: After nitriding is completed, preheat at heating temperature T2 and keep warm for time S2; Step 4: The surface of the sample after nitriding is subjected to laser cladding treatment, the cladding material is TC4 titanium alloy, the laser power is P, the defocus amount is L, the scanning speed is V1, the delivery rate is V2, the overlap rate is D, and the protective gas argon flow rate is V3, and a cladding layer with a thickness of D2 is obtained, and it is processed to a thickness of D3; Step 5: After the cladding is completed, keep the temperature at T4 for S3, then increase the temperature to T5 for S4, and repeat N times; Step 6: flame quench the surface of the processed sample, and control the moving rate to V4 to improve the surface structure; Step 7: The overall nitriding layer depth reaches D4, the nitriding layer hardness is H, and the pitting potential is increased to above E.

2. The method according to claim 1, characterized in that Step 2 includes: Step 21: Ion nitriding uses nitrogen-hydrogen mixed gas as the process gas, and the supply amount of ion nitriding process gas is set to 0.05m 3 / h~0.6m 3 / h; Step 22: using a nitrogen-hydrogen mixed gas as the process gas, wherein the volume content A of the nitrogen is set to 35%-55%, the volume content B of the hydrogen is set to 55%-35%, and the volume content C of the argon is set to 10%; Step 23: Process the parts by mechanical processing, and the surface appearance of the parts shall be free from defects such as rust, scratches, and bumps, and the roughness of the surface to be infiltrated shall not be greater than 0.8 μm; Step 24: Set the vacuum degree M to 10 -1 to 10 -3 Pa, the gas pressure in the furnace during the insulation stage ranges from 100Pa to 1300Pa; Step 25: The heating temperature in the furnace is T1, and the insulation time is S1; Step 26: After the insulation stage is over, cut off the glow power supply, close the valve to stop gas supply and exhaust, and the workpiece cools down with the furnace. The workpiece can be taken out of the furnace only when the temperature drops below 150°C; Step 27: Detect the depth of the penetration layer, and the penetration layer depth D1 is controlled within the range of 1.0-1.5 mm; Step 28: Detect the structure of the nitrided layer. The near-surface layer is γ′ phase and ε phase. Cr2N and CrN compounds can be formed on the surface. The content of the CrN compound is controlled to be above 75%; Step 29: If the content of CrN compound is lower than 75%, the nitrogen volume content A is set to the upper limit of the recommended value, and the nitriding temperature T1 is increased to 580-630°C.

3. The method according to claim 1, characterized in that Step 3 includes: Step 31: Use an air furnace to heat the nitrided sample, select the temperature T2, the heating temperature shall not exceed T3, the insulation time is S2, and cool with the furnace; Step 32: Detect the microstructure of the nitriding layer. The near-surface layer is γ′ phase and ε phase. Cr2N and CrN compounds can be formed on the surface. The content of the CrN compound is controlled to be above 75%. Step 33: If the content of CrN compound is less than 75%, a part of CrN compound has been converted into Cr2N, and supplementary nitriding is performed again; Step 34: Supplementary nitriding process, supplementary nitriding holding time S5; Step 35: Check the microstructure of the nitriding layer. The near-surface layer is γ′ phase and ε phase. Cr2N and CrN compounds can be formed on the surface, wherein the content of the CrN compound is controlled to be above 75%.

4. The method according to claim 1, characterized in that Step 4 includes: Step 41: Before the cladding process, the TC4 alloy powder is dried to prevent the powder from agglomerating and affecting fluidity; Step 42: Select the following process parameters: laser power P is 2200-3000W, defocus L is 0±3mm, scanning speed V4, powder feeding rate V2, overlap rate D is 40%-55%, shielding gas flow rate V3, double or triple cladding, and control the cladding layer thickness D2 within the range of 0.6-1.0mm; Step 43: remove the cladding layer on the surface by mechanical processing, and control the cladding layer D3 after processing to be within the range of 0.2-0.3 mm, and the surface roughness is not greater than 0.8 μm.

5. The method according to claim 1, characterized in that Step 5 includes: Step 51: according to the heating temperature T4, the holding time S3, the heating temperature T5, the holding time S40.5h, the number of cycles N is set to 3-7 times; Step 52: Check the appearance and organizational composition of the surface of the cladding layer. The surface should be golden yellow and covered with certain titanium nitrides, including Ti3N, Ti2N, and TiN. The content of TiN needs to be controlled at 30%-60%.

6. The method according to claim 1, characterized in that Step 6 includes: The surface of the sample clad with TC4 titanium alloy was flame quenched again, and the moving speed V4 was controlled within the range of 40-60 mm / min to increase the depth of the infiltration layer and adjust the structure in the cladding layer.

7. The method according to claim 1, characterized in that Step 7 includes: The overall nitriding layer depth reaches D4 of 1.5mm-2.0mm, the nitriding layer hardness H is 1050-1350HV, and the pitting potential is increased to E of more than 900mV.

8. The method according to claim 1, characterized in that The heating temperature T1 is set to 480℃-550℃; The heating temperature T2 is set to 200°C-350°C; The heating temperature T3 is set to 400°C; The heating temperature T4 is set to 750°C; The heating temperature T5 was set to 800°C.

9. The method according to claim 1, characterized in that: The holding time S1 is set to 6-12h; The holding time S2 is set to 1-2h; The holding time S3 is set to 1h; The holding time S4 ​​is set to 0.5h; The holding time S5 is set to 1-3h.

10. The method according to claim 1, characterized in that Scanning speed V1 is 600-800 mm / min; Scanning speed V4 is 600-1100 mm / min; The powder feeding rate V2 is 8-15g / min; The protective gas flow rate V3 is 6-8L / min.